Skills Lab Pädiatrie: Stärken kommunikativer Fertigkeiten für das Gespräch mit psychosozial belasteten Familien - Georg, Anna; Vidalón Blachowiak, Thorsten; Wiehmann, Janna; Al-Ameery-Brosche, Ines; Dierolf, Janna; Krämer, Julia; Berning, Anna; Hauschild, Sophie; Taubner, Svenja (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2024)
SUMMARY - - Pediatric Skills Lab: Strengthening Communication Skills for the Conversations with Psychologically burdened Families To identify psychosocially burdened families early and motivate them to seek further assistance is a central aspect of pediatric preventivemedicine.The aim of the feasibility study was to develop the Pediatric Skills Lab to promote methods for identifying and addressing psychosocially burdened families, and to evaluate it. Thirteen primary care pediatricians participated in two trials of the Pediatric Skills Lab, an interdisciplinary developed two-part digital training.They answered questions regarding their work with psychosocially burdened families and their satisfaction with the Pediatric Skills Lab. Overall, there was a high level of satisfaction reported with the Pediatric Skills Lab. Specifically, the presentation of results on the effects of psychosocial stressors, the practical exercises, and the exchange with colleagues during the interactive webinar were highly praised. Criticisms included, for example, the short duration of practical exercises and the lack of sufficient examples and live demonstrations. The Pediatric Skills Lab is a training concept tailored to meet the existing needs. With widespread implementation, it could enhance psychosocial care provision. Consideration should be given to extending the duration of the training to allow formore practical exercises. Future studies building upon this feasibility study should examine the effects of the training. Additionally, ways to integrate the Pediatric Skills Lab into existing curricula formedical education should be explored.